Fenomena Turunnya Minat Generasi Z di Jakarta Menjadi PNS: Pengaruh Teknologi, Gaya Hidup dan Perubahan Preferensi Kerja - Fotaleno, Fahmy (LITERATUS, 2024)
Generation Z in Jakarta has shown a significant decline in interest in becoming a civil servant, a phenomenon that is becoming increasingly evident among young people in the capital city. This research aims to identify and analyse the main factors influencing this generation's changing attitudes and career preferences towards civil servants. To gain a more in-depth picture, the methods used in this research include a review of relevant literature, as well as in-depth interviews with a number of representatives from Generation Z who are currently studying or have entered the workforce. These interviews provided direct insight into their views and aspirations for careers, particularly in the public sector. The results of this research revealed several key factors that have contributed to Generation Z's declining interest in joining the public sector, particularly in civil service positions. The first factor identified was a change in work preferences that increasingly prioritises flexibility, creative freedom, and a more dynamic work environment. Generation Z is more likely to be attracted to jobs that offer room to grow and channel their creativity, something that is perceived to be easier to obtain in the private sector or creative industries compared to the often rigid and bureaucratic public sector.